Designing the Concept of Good Corporate Governance in Family Company: (Case Study at CV. XYZ AMDK Company) - Fariz Achmad Ayuba (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
This research aims to design the principles of Good Corporate Governance in the bottled mineral water manufacturing company CV. XYZ. This company is a purely family company, which is one hundred percent family owned. This study uses a qualitative method with a case study approach. Data collection using interviews and documentation. Researchers interviewed the passive committee, directors, deputy directors, and Ciputra University lecturers as experts. After getting the data through interviews, the data were analyzed by examining data from various sources, after which the data was reduced, categorized, data validity and drawing conclusions. Testing the validity of the data using source triangulation. The result of this research shows that the company has indirectly implemented the concept of Good Corporate Governance such as transparency, responsibility, independence, and fairness. However, only the principle of Accountability has not been implemented, because the company has so far not had a clear organizational structure and no formal written policies and SOPs.